2023
DOI: 10.1590/0103-8478cr20210813
|View full text |Cite
|
Sign up to set email alerts
|

Natural extracts marination in chicken breast fillets

Abstract: This study evaluated the effects of natural extracts on chicken breast fillet marinades regarding the physicochemical properties, oxidative stability, and the Staphylococcus aureus and Escherichia coli inhibition during 21 days of storage. Chicken breast fillets (Pectoralis major) (128 units) purchased in a local market, were used, allocated in a completely randomized block design, in a 4 x 4 factorial scheme (antioxidant x storage time), totalling 16 treatments with eight replicates. The TBARS and the pH valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…However, herbs are a common ingredient in meat marinades not only for their flavourful qualities. They are also used because of their antioxidant [143,199,[202][203][204] and antimicrobial properties [66,143,178,205]. Rohod et al [204] demonstrated that rosemary and oregano have similar efficiencies to synthetic antioxidants such as BHT in inhibiting the development of Staphylococcus aureus in marinated chicken breast.…”
Section: Effect Of Marinades Based On Seasonings On the Quality Of Meatmentioning
confidence: 99%
See 2 more Smart Citations
“…However, herbs are a common ingredient in meat marinades not only for their flavourful qualities. They are also used because of their antioxidant [143,199,[202][203][204] and antimicrobial properties [66,143,178,205]. Rohod et al [204] demonstrated that rosemary and oregano have similar efficiencies to synthetic antioxidants such as BHT in inhibiting the development of Staphylococcus aureus in marinated chicken breast.…”
Section: Effect Of Marinades Based On Seasonings On the Quality Of Meatmentioning
confidence: 99%
“…They are also used because of their antioxidant [143,199,[202][203][204] and antimicrobial properties [66,143,178,205]. Rohod et al [204] demonstrated that rosemary and oregano have similar efficiencies to synthetic antioxidants such as BHT in inhibiting the development of Staphylococcus aureus in marinated chicken breast. The use of marinades with thyme and orange blends effectively reduced lipid oxidation in chicken meat, without a negative effect on the meat's sensory quality or colour parameters [178].…”
Section: Effect Of Marinades Based On Seasonings On the Quality Of Meatmentioning
confidence: 99%
See 1 more Smart Citation